Various Simulated Body Fluids Lead to Significant Differences in Collagen Tissue Engineering Scaffolds - Suchý, Tomáš; Bartoš, Martin; Sedláček, Radek; Šupová, Monika; Žaloudková, Margit; Martynková, Gražyna Simha; Foltán, René (Materials (Basel, Switzerland), 2021)
This study aims to point out the main drawback with respect to the design of simulated body environments. Three media commonly used for the simulation of the identical body environment were selected, i.e., Kokubo's simulated body fluid that simulates the inorganic component of human blood plasma, human blood plasma, and phosphate buffer saline. A comparison was performed of the effects of the media on collagen scaffolds. The mechanical and structural effects of the media were determined via the application of compression mechanical tests, the determination of mass loss, and image and micro-CT analyses. The adsorption of various components from the media was characterized employing energy-dispersive spectrometry. The phase composition of the materials before and after exposure was determined using X-ray diffraction. Infrared spectroscopy was employed for the interpretation of changes in the collagen secondary structure. Major differences in terms of the mechanical properties and mass loss were observed between the three media. Conversely, only minor structural changes were detected. Since no general recommendation exists for selecting the simulated body environment, it is necessary to avoid the simplification of the results and, ideally, to utilize alternative methods to describe the various aspects of degradation processes that occur in the media.
Keywords: micro-CT; blood plasma; collagen; XRD; porosity; mechanical properties; scaffold; structural parameters; simulated body fluid; mass loss